Clinical Bioequivalence of Wixela Inhub and Advair Diskus in Adults With Asthma - Ng, Dik (J Aerosol Med Pulm Drug Deliv, 2020)
Background: Wixela(®) Inhub(®) is a dry powder inhaler approved as a generic equivalent to Advair(®) Diskus(®) (fluticasone propionate [FP]/salmeterol fixed-dose combination) for patients with asthma or chronic obstructive pulmonary disease (COPD). This study aimed at confirming the local (lung) therapeutic equivalence of both the FP and salmeterol components of Wixela Inhub (test [T]) to Advair Diskus (reference [R]) after inhalation. Methods: This randomized, double-blind, double-dummy, placebo-controlled, parallel-group study in patients ≥18 years with mild-to-moderate persistent asthma compared the local therapeutic equivalence (using forced expiratory volume in 1 second [FEV(1)]) of FP/salmeterol (100/50 μg) after inhaled delivery via T and R. Results: Randomized patients (N = 1127) received T (n = 512), R (n = 512), or placebo (n = 103). T and R significantly increased day 1 FEV(1) area under the effect curve over 12 hours of the change from baseline (AUC([0–12])) and day 29 trough FEV(1) over placebo, indicating that these endpoints were sufficiently sensitive for evaluation of bioequivalence. On day 1, T and R each increased FEV(1) AUC((0–12)) over placebo (3.134 L•h [T], 2.677 L•h [R]; each p < 0.0001). Following twice-daily dosing for 28 days, T and R also each increased trough FEV(1) (measured on day 29) over placebo (235 mL [T], 215 mL [R]; each p < 0.0001). Least-squares mean T/R ratios (90% confidence intervals) for day 1 FEV(1) AUC((0–12)) and day 29 trough FEV(1) were 1.120 (1.016–1.237) and 1.069 (0.938–1.220), respectively, indicating that T and R were bioequivalent for both co-primary endpoints. FP/salmeterol was well tolerated when administered via either T or R. Conclusions: These results demonstrate that the therapeutic effects of Wixela Inhub are bioequivalent to Advair Diskus in the lung. Wixela Inhub represents a therapeutically equivalent new FP/salmeterol treatment option for use in the treatment of asthma and COPD.